Epidemiological characteristics and financial losses due to avian aspergillosis in households in the Almaty region, Republic of Kazakhstan - Kalkayeva, Dinara; Maulanov, Amangeldi; Sobiech, Przemysław; Michalski, Mirosław; Kuzembekova, Gulnur; Dzhangabulova, Ainur; Nurkhojayev, Nurzhan; Aldayarov, Nurbek (Frontiers in Veterinary Science, 2023)
Aspergillosis is a severe fungal disease that affects all species, ages of poultry and leads to significant economic losses within the poultry industry. The economic significance of aspergillosis is associated with direct losses due to poultry mortality, decline in the production of meat and eggs, feed conversion, and poor growth of recovering poultry. Although a decrease in the production of poultry meat and eggs in Kazakhstan due to this fungal disease has been widely reported, studies of the consequent financial losses on affected farms (households) have not been carried out. This study aimed to estimate the financial losses and epidemiological parameters of avian aspergillosis among households affected by the disease in the Almaty region. To achieve the objectives of the research, a survey was conducted involving affected households from February 2018 to July 2019. Affected poultry were diagnosed based on clinical, macroscopical, microscopical procedures and once the infection was confirmed, household owners were interviewed. Data were collected from 183 household owners. The median incidence rick and fatality rate were 39 and 26% in chickens, 42 and 22% in turkeys, 37 and 33% in geese, respectively, with young poultry having a higher incidence risk and fatality rate than adults. Some 92.4% of the household owners treated affected poultry using natural folk methods and 7.6% of household owners used antifungal drugs and antibiotics, spending a median of US$35.20 (min US$0; max US$400) per household throughout the course of the infection. Egg production was reduced by a median of 58.3% when households were affected. The price of poultry fell by a median 48.6% immediately after recovery due to weight loss. The median of overall financial losses of households were US$198.50 (min US$11; max US$1269). The majority of household owners (65%) did not replace their poultry, 9.8% household owners replaced all their poultry, the remaining 25.1% replaced only a proportion of the poultry lost at the time of the study. Newly acquired poultry were purchased from neighbors (10.9%), fellow villagers (50%) and state poultry farms (39.1%). This study indicates the direct financial losses in households due to aspergillosis in the Almaty region of Kazakhstan.